Hyperhydration of breast and skin cancers: effects on thermophysical tissue properties in clinical hyperthermia with water-filtered infrared-A radiation (wIRA) - an updated review - Helmut Piazena; Peter Vaupel (International Journal of Hyperthermia)
Background Water contents (Cw) of soft tissues are different and influence (a) the absorption of water-filtered infrared-A radiation (wIRA) used in superficial hyperthermia, (b) key parameters of the Pennes’ bioheat transfer equation, and (c) characteristics of heat exchange within and between tissues.Aim The effect of Cw on these parameters has been quantified for normal skin, female breast and corresponding malignancies with Cw values up to ≈ 1.6 times higher.Methods Literature data on spectral absorption and reduced scattering coefficient, density, specific heat capacity, thermal conductivity, diffusivity and effusivity of normal tissues and malignancies have been correlated with respective tissue water contents. Published in vivo data on wIRA-transmittance in human skin and underlying muscle have been experimentally extended to depths up to 11 mm.Results On average, the absorption of wIRA and the thermal tissue parameters increased linearly with Cw. Mean wIRA-penetration depth reached ≈ 2.9 mm at Cw ≈ 70 wt.%. While specific heat capacities, thermal conductivities, thermal diffusivities and thermal effusivities for melanoma and breast cancer exceeded those of corresponding normal tissues, heat capacities of both malignancies differed only slightly compared to the surrounding normal tissues. Despite small Cw values, maxima of absorbance coupled with low heat capacity and thermal conductivity occurred in the subcutaneous tissues.Conclusions These data indicate high efficacy of superficial wIRA-hyperthermia in clinical oncology when exposed to composite tissues with highly variable water and fat contents. Continuous monitoring of tissue temperature during irradiation is recommended to prevent hot spots and to ensure therapeutically relevant temperature fields.